Solid electrolyte, solid electrolyte layer, and solid electrolyte battery
By adjusting the composition and synthesis process of halide-based solid electrolytes, the problem of low ion conductivity is solved, and efficient battery charging and discharging performance is achieved.
Patent Information
- Application Number
- CN202380064111.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-12
- Publication Date
- 2025-04-25
AI Technical Summary
The existing halide-based solid electrolytes have low ion conductivity and are difficult to meet the demand for efficient battery charging and discharging.
By adjusting the composition and synthesis process of halide-based solid electrolytes, their ion conductivity is improved. Specific methods include introducing specific metal and anionic groups into the solid electrolyte, optimizing the molar ratio and synthesis conditions of the compound to improve its Raman spectral characteristics and ion conduction properties.
The high ion conductivity of solid electrolyte is achieved and the charge and discharge rate characteristics of solid electrolyte batteries are improved.
Smart Images

Figure CN119895502A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte, a solid electrolyte layer and a solid electrolyte battery.
[0002] This application claims priority based on Japanese Patent Application No. 2022-157983 filed in Japan on September 30, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] In recent years, electronic technology has developed rapidly, achieving small, light, thin and multifunctional portable electronic devices. As a result, for batteries that become power sources for electronic devices, there is a strong desire for small, light, thin and improved reliability, and solid electrolyte batteries using solid electrolytes as electrolytes have attracted much attention. As solid electrolytes, oxide solid electrolytes, sulfide solid electrolytes, complex hydride solid electrolytes, halide solid electrolytes, etc. are known.
[0004] For example, Non-Patent Document 1 states that the ion conductivity of Li3ScCl6 as a halide solid electrolyte is 3 mS / cm, and that the potential window on the reduction side is 0.91 V (V vs. Li / Li + ).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2022-122849
[0008] Non-patent literature
[0009] Non-patent literature 1: Jianwen Liang et al., J. Am. Chem. Soc., 2020, 142, pages 7012 to 7022.
[0010] Non-patent document 2: RJH Clark, "The impact of Laser-Raman spectroscopy on organic chemistry", The SPEX Speaker Vol. XVIII, No. 1 (March, 1973) Summary of the invention
[0011] Technical problem to be solved by the invention
[0012] It is generally believed that the ion conductivity of halide solid electrolytes is higher than that of oxide solid electrolytes, sulfide solid electrolytes, complex hydride solid electrolytes, etc. The ion conductivity (3mS / cm) of Li3ScCl6 recorded in non-patent document 1 is high, but it is subject to various restrictions, and sometimes the characteristics recorded in non-patent document 1 cannot be directly reflected or other substances have to be selected. Therefore, in solid electrolytes of the same structure, materials that can relatively improve ion conductivity are required.
[0013] Li2ZrCl6 and Li2Zr(SO4)Cl4, which are known as halide solid electrolytes (for example, see Patent Document 1), are solid electrolyte materials that use Zr, which has a high abundance in the earth's crust, as a central metal and are advantageous in terms of resources and cost. However, the ion conductivity is 4×10 -4 S / cm, the charge and discharge rate characteristics of a battery using this solid electrolyte are insufficient.
[0014] The present invention has been developed in view of the above-mentioned problems, and an object of the present invention is to provide a solid electrolyte, a solid electrolyte layer, and a solid electrolyte battery having high ion conductivity.
[0015] Technical solutions for solving technical problems
[0016] The present inventors have continued to conduct intensive research and succeeded in improving the ion conductivity without changing the composition of the halide-based solid electrolyte, thereby completing the present invention.
[0017] In order to solve the above problems, the present invention provides the following solutions.
[0018] A first aspect of the present invention provides a solid electrolyte comprising a compound represented by the following formula (1), wherein in a Raman spectrum detected by Raman spectroscopy, a solid electrolyte having a wavelength of 200 to 450 cm -1 Range and 80~200cm -1 There is a peak in the range of 200-450cm -1 The peak in the range of 80 to 200 cm is defined as the peak A, and the straight line connecting the starting point 1A and the starting point 2A of the peak A is defined as the baseline A, and the -1 When the peak in the range of is set as peak B, and the straight line connecting starting point 1B and starting point 2B of the peak B is set as baseline B, the peak A relative to the strongest peak P from baseline A A The peak width at half the intensity is 55 cm -1 Above, and the peak B relative to the strongest peak P from the baseline B B The peak width at half the intensity is 55 cm -1 above;
[0019] Li a A b E c J e X f H h ···(1)
[0020] (In formula (1), A is at least one element selected from alkali metals and alkaline earth metals other than Li, E is at least one element selected from Al, Ga, In, Sc, Y, Ti, Zr, Hf, and lanthanide elements, J is at least one group selected from anions, X is at least one element selected from F, Cl, Br, and I, 0.5≦a<6, 0≦b<6, 0<c<2, 0<e≦6, 0<f≦6.1, and 0≦h≦0.2.)
[0021] A second aspect of the present invention provides a solid electrolyte layer comprising the solid electrolyte of the first aspect.
[0022] A third aspect of the present invention provides a solid electrolyte battery comprising a solid electrolyte layer, a positive electrode, and a negative electrode, wherein at least one of the positive electrode and the negative electrode contains the solid electrolyte of the first aspect.
[0023] A fourth aspect of the present invention provides a solid electrolyte battery comprising the solid electrolyte layer of the second aspect, a positive electrode, and a negative electrode.
[0024] Effects of the Invention
[0025] According to the aspects of the present invention, a solid electrolyte having high ion conductivity can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a graph showing the Raman spectrum of Li 2 ZrSO 4 Cl 4 which has been made highly ion conductive as an example of the solid electrolyte according to the present embodiment.
[0027] Figure 2 It is used based on Figure 1 The graph in which the portion of the Raman spectrum enclosed by the dotted line indicated by P1 is enlarged is a diagram for explaining the evaluation method 1 of the Raman spectral characteristics.
[0028] Figure 3 This is a diagram for explaining evaluation method 2 of Raman spectral characteristics.
[0029] Figure 4 This is a diagram for explaining evaluation method 2 of Raman spectral characteristics.
[0030] Figure 5 It is a schematic cross-sectional view of the solid electrolyte battery of this embodiment.
[0031] Fig. 6A This is a diagram showing evaluation of Raman spectral characteristics of the Raman spectrum of Example 4 by evaluation method 1.
[0032] Figure 6B This is a diagram showing evaluation of the Raman spectroscopic characteristics of the Raman spectrum of Example 4 by evaluation method 2.
[0033] Fig. 7A This is a diagram showing evaluation of Raman spectral characteristics of the Raman spectrum of Example 25 by evaluation method 1.
[0034] Figure 7B This is a diagram showing evaluation of the Raman spectral characteristics of the Raman spectrum of Example 25 by evaluation method 2.
[0035] Figure 8 This is a diagram showing evaluation of Raman spectral characteristics of the Raman spectrum of Comparative Example 1 by Evaluation Method 1.
[0036] Fig. 9 This is a diagram showing evaluation of Raman spectral characteristics of the Raman spectrum of Comparative Example 2 by Evaluation Method 1.
[0037] Description of Reference Numerals
[0038] 10…Solid electrolyte layer
[0039] 20…Positive electrode
[0040] 22…Positive electrode collector
[0041] 24…Positive electrode mixture layer
[0042] 30…Negative
[0043] 32…Negative electrode collector
[0044] 34…Negative electrode mixture layer
[0045] 40…Power generation element
[0046] 50…outer body
[0047] 52…metal foil
[0048] 54…resin layer
[0049] 60, 62…terminals
[0050] 100…Solid electrolyte battery DETAILED DESCRIPTION
[0051] Hereinafter, the present embodiment will be described in detail with reference to the drawings as appropriate. In order to facilitate understanding of the features of the present invention, the drawings used in the following description sometimes enlarge the features for convenience, and sometimes the dimensional ratios of the components are different from the actual ones. The materials, dimensions, etc. exemplified in the following description are only examples, and the present invention is not limited to these, and the present embodiment can be appropriately changed within the scope of not changing its technical requirements.
[0052] The expression "a±b" indicates the range of the value from "ab" to "a+b". The expression "aE-b" indicates "a×10 -b ” value.
[0053] "Solid Electrolyte"
[0054] A solid electrolyte is a substance that can move ions when an electric field is applied from the outside. If the ion conductivity of the solid electrolyte is high, the transfer of ions in the solid electrolyte battery becomes smooth, and the internal resistance becomes small.
[0055] The solid electrolyte contains Li a A b E c J e X f H h ···Halide-based solid electrolyte represented by (1). The solid electrolyte may contain a material derived from a raw material powder in addition to the compound represented by the above formula (1). The material derived from the raw material powder is, for example, Li2SO4.
[0056] The solid electrolyte may be in the form of a powder (particle) or a sintered body after sintering the powder. In addition, the solid electrolyte may be a molded body formed by compressing the powder, a molded body formed by molding a mixture of powder and a binder, or a coating formed by applying a coating containing powder, a binder, and a solvent, followed by heating to remove the solvent. In addition, the main structure of the solid electrolyte may be amorphous or crystalline.
[0057] In formula (1), Li is a lithium ion. a satisfies 0.5≦a<6, preferably satisfies 2.0≦a≦4.0, and more preferably satisfies 2.5≦a≦3.5. When E is Zr or Hf, a is preferably 1.0≦a≦3.0, and more preferably 1.5≦a≦2.5. In the compound represented by formula (1), if a is 0.5≦a<6, the content of Li contained in the compound is appropriate, and the ion conductivity of the solid electrolyte layer 10 becomes high.
[0058] In formula (1), A is at least one element selected from alkali metals and alkaline earth metals other than Li. A is replaced by a part of Li ions. A is, for example, Na or Ca. If A is Na or Ca, the potential window on the reduction side of the solid electrolyte becomes wider. b satisfies 0≦b<6. In addition, a+b satisfies 0.5≦a+b<6.
[0059] In formula (1), E is an essential component and is at least one element selected from Al, Ga, In, Sc, Y, Ti, Zr, Hf, and lanthanide elements (La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu). E preferably contains Al, Sc, Y, Zr, Hf, and La, and more preferably contains Zr and Y. E improves the ionic conductivity of the solid electrolyte. c is 0<c<2. In order to more effectively obtain the effect brought about by containing E, c is preferably 0.6≦c. In addition, E is an element that forms the skeleton of the solid electrolyte. c is more preferably c≦1.
[0060] In formula (1), J is at least one group selected from anions. For example, the anion is selected from OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 、Si6O 18 、PO3、PO4、P2O7、P3O 10, SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO, OOC-CH2-COO, OOC- CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH2-COO, C6H5SO3, OOC-CH=CH-COO, C(OH)(CH2COOH)2COO, AsO4, BiO4, CrO4, MnO4, PtF6, PtCl6, PtBr6, PtI6, SbO 4. At least one group among SeO4, TeO4, HCOO, CH3COO, and O (BOB is a disodium oxalate borate ion, OOC-(CH2)2-COO is an anion of succinic acid, OOC-CH2-COO is an anion of malonic acid, OOC-CH(OH)-CH(OH)-COO is an anion of tartaric acid, OOC-CH(OH)-CH2-COO is an anion of malic acid, C6H5SO3 is an anion of benzenesulfonic acid, OOC-CH=CH-COO (trans type) is an anion of fumaric acid, OOC-CH=CH-COO (cis type) is an anion of maleic acid, and C(OH)(CH2COOH)2COO is an anion of citric acid.).
[0061] By selecting the above-mentioned anions as the group, high ion conductivity can be obtained and the reduction resistance can be improved.
[0062] e satisfies 0≦e≦6. In order to make the effect of widening the potential window on the reduction side by containing J more significant, e is preferably 0.5≦e. e is preferably e≦3 so as not to cause a decrease in the ion conductivity of the solid electrolyte due to an excessive J content.
[0063] X is at least one selected from F, Cl, Br, and I. In order to improve the ionic conductivity of the solid electrolyte, X is preferably at least one selected from Cl, Br, and I, preferably contains either or both of Br and I, and particularly preferably contains I. When X contains F, in order to obtain a solid electrolyte with high ionic conductivity, X preferably contains F and two or more selected from Cl, Br, and I.
[0064] If X is F, it becomes a solid electrolyte with sufficiently high ion conductivity and excellent oxidation resistance. If X is Cl, it becomes a solid electrolyte with high ion conductivity and a good balance between oxidation resistance and reduction resistance. If X is Br, it becomes a solid electrolyte with sufficiently high ion conductivity and a good balance between oxidation resistance and reduction resistance. If X is I, it becomes a solid electrolyte with high ion conductivity.
[0065] f satisfies 0<f≦6.1. f is preferably 1≦f. If f is 1≦f, when the solid electrolyte is press-formed into a pellet, the strength of the pellet becomes high. In addition, if f is 1≦f, the ion conductivity of the solid electrolyte becomes high. In addition, f is preferably f≦5 so that the sulfate is not insufficient due to excessive content of X and the potential window of the solid electrolyte is not narrowed.
[0066] In the formula (1), H is hydrogen and h satisfies 0≦h≦0.2.
[0067] Examples of the solid electrolyte include Li2ZrSO4Cl4, Li3YSO4Cl4, Li3ScSO4Cl4, and Li3InSO4Cl4.
[0068] (Raman spectral characteristics (evaluation method 1))
[0069] The solid electrolyte of the present embodiment has a Raman spectrum detected by Raman spectroscopy at 200 to 450 cm -1 Range and 80~200cm -1 There is a peak in the range of 200-450cm -1 The peak in the range of 80 to 200 cm is defined as the peak A, and a baseline A connecting the starting point 1A and the starting point 2A of the peak A is set. -1 The peak in the range is set as peak B, and when the baseline B connecting the starting point 1B and the starting point 2B of the peak B is set, the peak width of the peak A relative to half the intensity of the strongest peak from the baseline A is 55 cm -1 and the peak width of the peak B relative to half the intensity of the strongest peak from the base line B is 55 cm -1 The Raman spectroscopic characteristics based on the evaluation method 1 will be described in detail below.
[0070] Here, in Raman spectroscopy, light is incident on a substance, and the substance is evaluated by Raman scattered light having a wavelength different from that of the incident light. However, the wavelength difference between the Raman scattered light and the incident light is equivalent to the energy part of the vibration possessed by the substance, and therefore, various physical properties of the substance can be investigated based on the Raman spectrum. The inventors have conducted intensive research and found that the ion conductivity can be improved without changing the composition, and the improvement in ion conductivity is related to the characteristics of the Raman spectrum.
[0071] In the case of a solid having a regular lattice and high crystallinity, the peaks corresponding to each vibration energy become sharp (sharp shape), but the broad peaks reflect the disorder of crystallinity (promotion of amorphous structure). The present inventors found that the ion conductivity becomes higher by synthesizing a solid electrolyte in a manner that reduces the crystallinity (promotes the amorphous structure) even with the same composition, and that the promotion of the amorphous structure is reflected in the Raman spectrum and the peaks become broad, and came up with the present invention.
[0072] The “peak portion” is an overlap of multiple peaks. In the solid electrolyte, which is the object of this embodiment, the overlap of multiple peaks is between 200 and 450 cm -1 Range and 80~200cm -1 The "peak" reflects the overlap of peaks and has strong and weak fluctuations, but except for the starting point of the baseline, that is, the two points of contact with the spectrum, the "peak" does not touch the baseline A and the baseline B (when not in contact, it is evaluated as the same "peak").
[0073] Figure 1 This is a graph showing the Raman spectrum (20 to 1000 cm) of Li2ZrSO4Cl4 with high ion conductivity as an example of the solid electrolyte of the present embodiment. -1 ). Figure 2 Yes Figure 1 The enlarged graph of the portion of the Raman spectrum surrounded by the dotted line indicated by P1 (50 to 500 cm -1 ).
[0074] use Figure 1 and Figure 2 A method 1 for evaluating the Raman spectroscopic characteristics of the solid electrolyte according to the present embodiment will be described.
[0075] exist Figure 1 In FIG. 1 , the spectrum of the portion surrounded by the dotted line represented by P1 is a spectrum derived from the vibration energy of the metal (M)-halogen (X) bond. In the Raman spectrum detected by Raman spectroscopy, the heavier the M or X, the more the peak shifts to the lower wave number side.
[0076] In Non-Patent Document 2 Figure 8 In the figure, if X is changed to Cl, Br, or I, the peak shifts to the lower wave number side. The number of peaks here depends on the compound, but these peaks overlap to form two peaks, one of which is at 200 to 450 cm -1 The other peak is between 80 and 200 cm -1 range.
[0077] In the example of the Li-Sc-Cl based compound in Non-Patent Document 1, Sc is lighter than Zr and has a mass of 200 to 450 cm-1, compared to the above-mentioned example of the Li-Zr-Cl based compound.-1 The peak at 200 cm -1 The following peaks are on the high wave number side, and are included in the scope of this embodiment.
[0078] Even if M or X of the Li—M (metal)—X (halogen) compound is changed, it is considered that the peak derived from the MX bond is included in the scope of the present embodiment.
[0079] exist Figure 2 Raman spectrum (50~500cm -1 ), there are two peaks, a peak represented by the figure mark A (hereinafter, sometimes referred to as "peak A") and a peak represented by the figure mark B (hereinafter, sometimes referred to as "peak B") .
[0080] In this specification, a "peak" (in Figure 2 In the figure, the peak A is indicated by the reference numeral A, and the peak B is indicated by the reference numeral B).
[0081] Parallel to the horizontal axis and with a wave number of 50 to 500 cm -1 The straight line with a long range moves toward the side with higher relative intensity while being parallel to the horizontal axis. The point where the straight line first contacts the Raman spectrum is called the “starting point 1A” (at Figure 2 Starting point 1A is the relative intensity between 50 and 500 cm -1 The straight line is tilted with the starting point 1A as a reference (fixed).
[0082] Here, the starting point 1A is at 350 cm in the Raman spectrum. -1 When the wave number is above 1, the straight line is rotated counterclockwise with the starting point 1A as the reference (fixed), and the point where it contacts the Raman spectrum is called "starting point 2A" (at Figure 2 The straight line connecting the starting point 1A and the starting point 2A is called the baseline A (in FIG. Figure 2 In the figure, the reference numeral BL A The portion between the baseline A and the Raman spectrum is the peak A. In addition, when determining the starting point 2A, the wave number from the starting point 1A is 30 cm -1 When the straight line touches the Raman spectrum at a wave number position in a small range, the starting point 2A is not determined as the point, but the starting point 2A is determined at a position after the rise in intensity in front of the point reaches the peak.
[0083] Here, in the Raman spectrum, the starting point 1A is below 350 cm -1 In the case of the position of the wave number of, the straight line is rotated clockwise with the starting point 1A as a reference, and the point where it contacts the Raman spectrum is called the starting point 2A.
[0084] Next, parallel to the horizontal axis and with a wave number of 50 to 500 cm -1 The straight line with a long range moves from the side with high relative intensity to the side with low relative intensity while being parallel to the horizontal axis. On the wave number side lower than the peak A, the straight line moves from the point where the straight line first contacts the Raman spectrum to the side with low relative intensity, and the point just before the straight line first leaves the Raman spectrum is set as the "starting point 1B" (at Figure 2 In the Raman spectrum, the starting point 1B is below 150 cm -1 In the case of the position of the wave number, the straight line is rotated counterclockwise with the starting point 1B as the reference (fixed), and the point just before leaving the Raman spectrum is set as the "starting point 2B" (at Figure 2 The straight line between the starting point 1B and the starting point 2B is called the baseline B (in Figure 2 In the figure, the reference numeral BL B The portion between the baseline B and the Raman spectrum is the peak B. In addition, when determining the starting point 2B, the wave number from the starting point 1B is 30 cm -1 When the wave number position in a small range deviates from the Raman spectrum in a straight line, this point is not determined as the starting point 2B, but the starting point 2B is determined at a position after the rise in intensity in front of it reaches the peak.
[0085] Here, in the Raman spectrum, the starting point 1B is at 150 cm -1 When the wave number is above, the straight line is rotated clockwise with the starting point 1B as a reference, and the point immediately before it leaves the Raman spectrum is called the starting point 2B.
[0086] The peaks A and B thus identified exist at 200 to 450 cm-1, respectively, in the Raman spectrum of the solid electrolyte of the present embodiment. -1 Range, 80~200cm -1 range.
[0087] The above, based on Figure 2 The method of determining the peak A and the peak B is described for the Raman spectrum of , but the peak A and the peak B can also be determined by the same method for other Raman spectra.
[0088] In each of peak A and peak B, the peak with the largest wave number relative intensity is called the "strongest peak". Figure 2 In the figure, the reference numeral P A , Reference numeral P B The apexes of the peaks shown are the strongest peak of peak part A and the strongest peak of peak part B, respectively.
[0089] In the solid electrolyte of the present embodiment, the peak portion A has a peak P with respect to the strongest peak P from the base line A. A Strength (h A1 +h A2 ) half intensity h A1 The peak width w A 55cm -1 Above, and the peak B relative to the strongest peak P from the baseline B B Strength (h B1 +h B2 ) half intensity h B1 The peak width w B 55cm -1 above.
[0090] exist Figure 2 In the case of Li2ZrSO4Cl4 with high ion conductivity shown in the figure, the peak width w A 121.7cm -1 , peak width w B 85.7cm -1 In addition, in Li2ZrSO4Cl4 that has not been made highly ion conductive, the peak width w A 53.6cm -1 , peak width w B 64.9cm -1 .
[0091] In the solid electrolyte of this embodiment, it is preferred that the peak width w A 55cm -1 Above, and the peak width w B 66cm -1 More preferably, the peak width w B 80cm -1 above.
[0092] In the solid electrolyte of this embodiment, the strongest peak P in the peak portion B is B The wave number is preferably 140 cm -1 the following.
[0093] 80~200cm -1 The Raman spectrum in the range of 200 nm is a peak caused by the bending of the metal-halogen bond, and has a wide half-value width. At the same time, the peak position is shifted to the low wave number side, and a metal-halogen bond with a wide energy distribution can be easily formed. + The conduction path of ions exhibits high ionic conductivity.
[0094] (Raman spectral characteristics (evaluation method 2))
[0095] The solid electrolyte of the present embodiment has a Raman spectrum detected by Raman spectroscopy at 400 to 1000 cm -1 The straight line passing through the minimum point X and the second smallest minimum point Y in the region is set as the baseline C, and the strongest peak P of the peak part A is set as A and the strongest peak P of the peak B B When the intensities from the baseline C are IA and IB respectively, and the intensity between the peak A and the peak B at which the intensity from the baseline C becomes the minimum is IC, 0<IC.
[0096] Due to the disorder of the crystal structure, the distribution of metal-halogen binding energy expands, resulting in expansion toward the lower limit side of the vibration mode of the lower limit of the region of peak A and expansion toward the upper limit side of the vibration mode of the upper limit of the region of peak B, and the distinction between the two peak regions becomes blurred. As a result, Li + The probability of ion movement increases, resulting in high ion conductivity.
[0097] Hereinafter, the Raman spectral characteristics based on the evaluation method 2 will be described in detail.
[0098] use Figure 3 and Figure 4 Evaluation method 2 of the Raman spectroscopic characteristics of the solid electrolyte according to the present embodiment will be described.
[0099] First, if Figure 3 As shown, 400~1000cm -1 A line passing through point X having the minimum relative intensity and point Y having the second smallest minimum relative intensity in the region is set as baseline C.
[0100] Then, if Figure 4 As shown, the strongest peak P of the peak part A is A and the strongest peak P of the peak B B The intensities from the baseline C are denoted as IA and IB respectively, and the intensity between the peak A and the peak B at which the intensity from the baseline C becomes the minimum is denoted as IC, 0<IC.
[0101] In the solid electrolyte of this embodiment, it is preferred that the strongest peak P of the peak portion A is A The intensity IA and the minimum intensity IC satisfy 0.2≦IC / IA≦0.6.
[0102] In the solid electrolyte of the present embodiment, it is preferred that the strongest peak P of the peak portion B is B The intensity IB and the minimum intensity IC satisfy 0.1≦IC / IB≦0.6.
[0103] In the solid electrolyte of the present embodiment, it is preferred that the strongest peak P of the peak portion A is AThe intensity of IA and the strongest peak P of peak B B The strength IB satisfies IA<IB.
[0104] The solid electrolyte of the present embodiment preferably has peaks at 170±0.5 eV (chemical state of sulfur corresponds to SO 4 ) and 532±0.5 eV (chemical state of oxygen corresponds to SO 4 ) in a photoelectron spectrum measured by X-ray photoelectron spectroscopy (XPS).
[0105] The SO4 structure is maintained by the strong bonding of sulfur and oxygen in the solid electrolyte and exists in the solid electrolyte material, promoting the amorphous structure and easily forming Li + The conduction path of ions exhibits high ionic conductivity.
[0106] The solid electrolyte of the present embodiment preferably has peaks at 132.5±0.5 eV (chemical state of phosphorus corresponds to PO 4 ) and 531.5±0.5 eV (chemical state of oxygen corresponds to PO 4 ) in a photoelectron spectrum measured by X-ray photoelectron spectroscopy (XPS).
[0107] The PO4 structure is maintained by the strong bonding of sulfur and oxygen in the solid electrolyte and exists in the solid electrolyte material, promoting the amorphous structure and easily forming Li + The conduction path of ions exhibits high ionic conductivity.
[0108] "Solid electrolyte battery"
[0109] Figure 5 1 is a schematic cross-sectional view of a solid electrolyte battery 100 according to the present embodiment. Figure 5 The solid electrolyte battery 100 shown in the figure includes a power generation element 40 and an outer casing 50. The outer casing 50 covers the periphery of the power generation element 40. The power generation element 40 is connected to the outside via a pair of terminals 60 and 62. Figure 1 Although a stacked battery is shown in FIG. 1 , a wound battery may be used. The solid electrolyte battery 100 is used for, for example, a laminate battery, a square battery, a cylindrical battery, a coin battery, a button battery, and the like.
[0110] <Power generation element>
[0111] The power generation element 40 includes a solid electrolyte layer 10, a positive electrode 20, and a negative electrode 30. The power generation element 40 is charged or discharged by transfer of ions between the positive electrode 20 and the negative electrode 30 via the solid electrolyte layer 10 and transfer of electrons via an external circuit.
[0112] (Solid electrolyte layer)
[0113] The solid electrolyte layer 10 is a layer containing the solid electrolyte of the present embodiment. The solid electrolyte layer 10 may be only the solid electrolyte of the present embodiment, or may be used together with a support such as a binder or a nonwoven fabric. The binder may be the same as that used for the electrode.
[0114] The ratio of the binder to the solid electrolyte is preferably 10% or less by volume. The support such as nonwoven fabric may have insulating properties like the resin, ceramic, glass, etc. used for the binder, and the numerical aperture is preferably 85% or more.
[0115] The solid electrolyte layer 10 is sandwiched between the positive electrode 20 and the negative electrode 30. The solid electrolyte layer 10 includes a solid electrolyte that allows ions to move by a voltage applied from the outside. For example, the solid electrolyte conducts lithium ions and blocks the movement of electrons.
[0116] The solid electrolyte layer 10 is, for example, a halogenide solid electrolyte. The solid electrolyte layer 10 contains, for example, the above-mentioned solid electrolyte. When the positive electrode 20 or the negative electrode 30 contains the above-mentioned solid electrolyte, the solid electrolyte contained in the solid electrolyte layer 10 may not be the above-mentioned substance.
[0117] (positive electrode)
[0118] like Figure 5 As shown, the positive electrode 20 includes a plate-shaped (foil-shaped) positive electrode current collector 22 and a positive electrode mixture layer 24. The positive electrode mixture layer 24 is in contact with at least one surface of the positive electrode current collector 22.
[0119] The positive electrode current collector 22 can be any material that is resistant to oxidation and corrosion during charging and has electron conductivity. The positive electrode current collector 22 is, for example, a metal such as aluminum, stainless steel, nickel, titanium, or a conductive resin. The positive electrode current collector 22 may be in the form of powder, foil, stamping, or expansion.
[0120] The positive electrode mixture layer 24 contains a positive electrode active material and, if necessary, contains a solid electrolyte, a binder, and a conductive aid.
[0121] The positive electrode active material is not particularly limited as long as it can reversibly adsorb and release, insert and deintercalate (intercalation and deintercalation) lithium ions, and the positive electrode active material used in the known solid electrolyte battery can be used. As the positive electrode active material, for example, lithium-containing metal oxides, lithium-containing metal phosphates, etc. can be cited.
[0122] Lithium-containing metal oxides include, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), and lithium nickel oxide (LiNiO2). x Co y Mn zO2 (x + y + z = 1) represented by a composite metal oxide, lithium vanadium compounds (LiVOPO4, Li3V2 (PO4) 3), olivine-type LiMPO4 (wherein M represents at least one selected from Co, Ni, Mn, Fe), lithium titanate (Li4Ti5O 12 )wait.
[0123] In addition, the positive electrode active material may not contain lithium. As such positive electrode active materials, metal oxides (MnO2, V2O5, etc.) that do not contain lithium, metal sulfides (MoS2, etc.) that do not contain lithium, fluorides (FeF3, VF3, etc.) that do not contain lithium, etc., can be cited. When using a positive electrode active material that does not contain lithium, lithium ions are pre-doped into the negative electrode, or a negative electrode containing lithium ions is used.
[0124] The solid electrolyte contained in the positive electrode 20 is, for example, the above-mentioned solid electrolyte. The solid electrolyte contained in the positive electrode 20 may be a halide-based solid electrolyte other than the above-mentioned solid electrolyte.
[0125] The content of the solid electrolyte in the positive electrode mixture layer 24 is not particularly limited, but is preferably 1 to 50% by mass, more preferably 5 to 30% by mass, based on the total mass of the positive electrode active material, solid electrolyte, conductive additive, and binder.
[0126] The binder binds the positive electrode active material, the solid electrolyte, and the conductive additive to each other in the positive electrode mixture layer 24, and firmly bonds the positive electrode mixture layer 24 and the positive electrode collector 22. The positive electrode mixture layer 24 preferably contains a binder. The binder preferably has oxidation resistance and good adhesion.
[0127] As the binder for the positive electrode mixture layer 24, polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid (PA) and its copolymer, metal ion crosslinked body of polyacrylic acid (PA) and its copolymer, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or mixtures thereof, etc. Among them, PVDF is particularly preferably used as the binder.
[0128] The content of the binder in the positive electrode mixture layer 24 is not particularly limited, and is preferably 1% to 15% by mass, and more preferably 3% to 5% by mass, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive aid, and the binder. If the amount of the binder is too small, the positive electrode 20 with sufficient bonding strength tends to be unable to be formed. On the contrary, if the amount of the binder is too large, the ordinary binder is electrochemically inactive, and therefore, does not contribute to the discharge capacity, and it tends to be difficult to obtain a sufficient volume or mass energy density.
[0129] The conductive aid improves the electronic conductivity of the positive electrode mixture layer 24. The conductive aid can use a known conductive aid. The conductive aid is, for example, a carbon material such as carbon black, graphite, carbon nanotubes, graphene, a metal such as aluminum, copper, nickel, stainless steel, iron, amorphous metal, a conductive oxide such as ITO, or a mixture thereof. The conductive aid can also be in the form of powder or fiber.
[0130] There is no particular limitation on the content of the conductive aid in the positive electrode mixture layer 24. When a conductive aid is added, the mass ratio of the conductive aid is preferably 0.5 mass % to 20 mass %, more preferably 1 mass % to 5 mass %, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive aid, and the binder.
[0131] (negative electrode)
[0132] like Figure 5 As shown, the negative electrode 30 includes a negative electrode current collector 32 and a negative electrode mixture layer 34 . The negative electrode mixture layer 34 is in contact with the negative electrode current collector 32 .
[0133] The negative electrode current collector 32 only needs to have electron conductivity. The negative electrode current collector 32 is, for example, a metal such as copper, aluminum, nickel, stainless steel, iron, or a conductive resin. The negative electrode current collector 32 may be in the form of powder, foil, stamping, or expansion.
[0134] The negative electrode mixture layer 34 contains a negative electrode active material and, if necessary, a solid electrolyte, a binder, and a conductive aid.
[0135] The negative electrode active material is not particularly limited as long as it can reversibly adsorb and release lithium ions, and insert and desorb lithium ions. The negative electrode active material can be any negative electrode active material used in known solid electrolyte batteries.
[0136] The negative electrode active material is a carbon material such as natural graphite, artificial graphite, mesophase carbon microbeads, mesophase carbon microspheres (MCF), coke, glassy carbon, organic compound calcined products, etc., which can react with Si, SiO x , Sn, aluminum and other lithium-compounded metals, their alloys, composite materials of these metals and carbon materials, lithium titanate (Li4Ti5O 12), oxides such as SnO2, metallic lithium, etc. The negative electrode active material is preferably natural graphite.
[0137] The solid electrolyte contained in the negative electrode 30 is, for example, the above-mentioned solid electrolyte. The solid electrolyte contained in the negative electrode 30 may be a halogenated solid electrolyte other than the above-mentioned solid electrolyte.
[0138] The binder and the conductive aid contained in the negative electrode 30 are the same as the binder and the conductive aid contained in the positive electrode 20 .
[0139] <Exterior body>
[0140] The outer casing 50 accommodates the power generation element 40 therein. The outer casing 50 prevents moisture and the like from entering the interior from the outside. Figure 5 As shown, the outer package 50 includes a metal foil 52 and a resin layer 54 laminated on each surface of the metal foil 52. The outer package 50 is a metal laminate film in which the metal foil 52 is coated with the resin layer 54 from both sides.
[0141] The metal foil 52 is, for example, an aluminum foil or a stainless steel foil. The resin layer 54 can be, for example, a resin film such as polypropylene. The material constituting the resin layer 54 may be different on the inside and outside. For example, as the material on the outside, a high-melting-point polymer such as polyethylene terephthalate (PET) or polyamide (PA) can be used, and as the material on the inside, polyethylene (PE) or polypropylene (PP) can be used.
[0142] <Terminal>
[0143] Terminals 60 and 62 are connected to the positive electrode 20 and the negative electrode 30, respectively. The terminal 60 connected to the positive electrode 20 is a positive terminal, and the terminal 62 connected to the negative electrode 30 is a negative terminal. Terminals 60 and 62 are responsible for electrical connection with the outside. Terminals 60 and 62 are formed of conductive materials such as aluminum, nickel, and copper. The connection method can be welding or screwing. In order to prevent short circuits, terminals 60 and 62 are preferably protected by insulating tape.
[0144] [Method for manufacturing solid electrolyte battery]
[0145] Next, the manufacturing method of the solid electrolyte battery of the present embodiment is described. First, a solid electrolyte is prepared. For example, raw material powders containing specified elements are mixed at a specified molar ratio, and a solid electrolyte can be manufactured by a mechanochemical reaction method. When the mechanochemical reaction is performed, the unreacted raw material is adjusted in a manner that remains in the solid electrolyte. Specifically, by changing the rotation speed, revolution speed, synthesis time, and state of the raw material powder at the time of input of the planetary ball mill, the unreacted components of the raw material can remain.
[0146] Regarding the solid electrolyte of the present embodiment, in order to improve the ion conductivity even with the same composition, the solid electrolyte is synthesized in a manner that the crystallinity becomes lower (promotes the amorphous structure). In this synthesis method, the raw material powder is synthesized while the synthesis is performed in a manner that suppresses excessive crystallinity. If such synthesis can be performed, there is no restriction on the adjustment method. In particular, it is found that the immediate cooling after the start of the synthesis, the shortening of the synthesis time (depending on the solid electrolyte, the synthesis time performed in the past is different, but for each type of solid electrolyte, the synthesis time is shorter than the previous synthesis time), the adjustment of the dew point when the raw material powder is put in and the closed operation of the container is very important.
[0147] When the halide raw material is contained in the raw material powder, the halide raw material is easy to evaporate when the temperature is increased. Therefore, the halogen gas can also be made to coexist in the atmosphere during sintering to supplement the halogen. In addition, when the halide raw material is contained in the raw material powder, it is also possible to sinter by hot pressing using a mold with high airtightness. In this case, the mold has high airtightness, so the evaporation of the halide raw material caused by sintering can be suppressed. By sintering in this way, a solid electrolyte in the state of a sintered body composed of a compound having a specified composition is obtained.
[0148] Next, the positive electrode 20 is prepared. The positive electrode 20 is produced by applying a paste containing a positive electrode active material onto the positive electrode current collector 22 and drying it to form a positive electrode mixture layer 24. The above-mentioned solid electrolyte may be added to the paste containing the positive electrode active material.
[0149] Next, the negative electrode 30 is prepared. The negative electrode 30 is produced by applying a paste containing a negative electrode active material onto the negative electrode current collector 32 and drying it to form a negative electrode mixture layer 34. The above-mentioned solid electrolyte may be added to the paste containing a negative electrode active material.
[0150] The power generation element 40 can be manufactured using a powder molding method, for example. A guide having a hole is provided on the positive electrode 20, and a solid electrolyte is filled into the guide. Then, the surface of the solid electrolyte is flattened, and the negative electrode 30 is overlapped on the solid electrolyte. Thus, the solid electrolyte is sandwiched between the positive electrode 20 and the negative electrode 30. Then, by applying pressure to the positive electrode 20 and the negative electrode 30, the solid electrolyte is press-formed. By press-forming, a laminated body in which the positive electrode 20, the solid electrolyte layer 10, and the negative electrode 30 are sequentially stacked is obtained.
[0151] Next, external terminals are welded to the positive electrode collector 22 of the positive electrode 20 and the negative electrode collector 32 of the negative electrode 30 forming the stacked body by a known method, respectively, and the positive electrode collector 22 or the negative electrode collector 32 and the external terminal are electrically connected. Then, the stacked body connected to the external terminal is housed in the outer body 50, and the opening of the outer body 50 is heat-sealed to thereby seal it. Through the above steps, the solid electrolyte battery 100 of this embodiment is obtained.
[0152] Since the solid electrolyte battery 100 of the present embodiment contains the above-mentioned solid electrolyte, the conduction of Li ions is smooth and the internal resistance is low.
[0153] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but each structure in each embodiment and their combination are merely examples, and the structure of the present embodiment can be added, omitted, replaced, and otherwise modified without departing from the technical requirements of the present invention.
[0154] Example
[0155] "Example 1"
[0156] (Preparation of solid electrolyte)
[0157] In a glove box with a dew point of about -75°C, zirconium chloride (ZrCl4) and lithium sulfate (Li2SO4) are weighed in a molar ratio of 1:8, and placed in a zirconia sealed container for a planetary ball mill with zirconia balls placed in advance. Next, the sealed container is covered, the lid is screwed to the container body, and the lid and the container are further sealed with polyimide tape. Polyimide tape has the effect of isolating moisture. Next, the zirconia sealed container is installed on the planetary ball mill. The rotation speed is set to 300 rpm and the revolution speed is set to 300 rpm. The rotation direction of the rotation and the revolution direction are set to opposite directions. The mechanochemical reaction is carried out for 2.5 hours to synthesize the solid electrolyte (Li4Zr 0.25 (SO4)2Cl). The synthesis was performed while cooling the lid of the zirconia sealed container so that the amount of change in temperature became 10°C or less one hour after the start of the synthesis.
[0158] The planetary ball mill is set in a normal atmosphere (air). The zirconia sealed container used in the planetary ball mill is screwed and further sealed with a polyimide tape. When the zirconia sealed container is installed in the planetary ball mill, the zirconia sealed container is firmly pressed and fixed. Therefore, it is believed that even in a normal atmosphere, moisture will hardly mix into the zirconia sealed container from the air.
[0159] <Measurement of Raman Spectrum>
[0160] The Raman spectrum of the solid electrolyte of Example 1 was measured by Raman spectroscopy.
[0161] The measurement conditions of the Raman spectrum are as follows: laser wavelength: 532 nm, slit width: 100×1000 μm, aperture: 40 μm, exposure time: 60 sec, and accumulation: twice.
[0162] Determine 200-450cm by evaluation method 1 -1 The peak A in the range of 80 to 200 cm -1 and measure the strongest peak and half-value width in each peak.
[0163] In addition, by evaluation method 2, the base line C is determined, and the strongest peak P of the peak part A is measured. A and the strongest peak P of peak B B The intensities IA and IB from the baseline C and the intensity between the peak A and the peak B from the baseline C become the minimum intensity IC.
[0164] <XPS measurement>
[0165] In addition, the photoelectron spectrum of the solid electrolyte of Example 1 was measured by X-ray photoelectron spectroscopy. The sample was collected in a glove box with a dew point of about -70°C in which argon gas was circulated, and transported to the XPS measuring device without being exposed to the atmosphere. The photoelectron spectrum was measured using Quantera2 manufactured by PHI. As a result, peaks were confirmed at 170±0.5 eV and 532±0.5 eV in the prepared solid electrolyte.
[0166] <Measurement of ion conductivity>
[0167] Next, in a glove box with a dew point of about -70°C in which argon gas was circulated, the obtained solid electrolyte powder was filled into a press-molding die and press-molded at a load of about 30 kN to produce a cell for measuring ion conductivity.
[0168] The die for press molding was composed of a PEEK (polyetheretherketone) cylinder with a diameter of 10 mm, and an upper punch and a lower punch made of SKD11 material with a diameter of 9.99 mm.
[0169] Then, a stainless steel disc and a Teflon (registered trademark) disc with a diameter of 50 mm and a thickness of 5 mm having threaded holes at four locations were prepared, and the pressurized mold was installed as follows. The stainless steel disc / Teflon (registered trademark) disc / pressurized mold / Teflon (registered trademark) disc / stainless steel disc were loaded in the order of the four screws with a torque of about 3 N·m. In addition, screws were inserted into the screw holes provided on the sides of the upper and lower punches, and set as external connection terminals.
[0170] The external connection terminal was connected to a potentiostat (VersaSTAT3 manufactured by Princeton Applied Research) equipped with a frequency response analyzer, and the ionic conductivity was measured using the impedance measurement method. The measurement was performed at a frequency range of 1 MHz to 0.1 Hz, an amplitude of 10 mV, and a temperature of 25°C. The ionic conductivity of the solid electrolyte of Example 1 was 1.1×10 -3 S / cm.
[0171] The composition, molar ratio and measurement results of each raw material are summarized in Tables 1, 2 and 7 below.
[0172] In Tables 7 and 8, the peak A(B) is expressed as the strongest peak P relative to the baseline A(B). A (P B ) is recorded as the "half-value width".
[0173] "Examples 2 to 8"
[0174] In Examples 2 to 8, solid electrolytes were synthesized in the same manner as in Example 1 except that the materials and / or molar ratios of the raw material powders and the synthesis time were changed. In Examples 2 to 8, the physical properties of the solid electrolytes were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 1, 2, and 7 below.
[0175] In addition, Fig. 6A 2 shows a graph showing the evaluation of the Raman spectroscopic characteristics of the Raman spectrum of Example 4 by evaluation method 1. Figure 6B 3 is a diagram showing evaluation of the Raman spectroscopic characteristics of the Raman spectrum of Example 4 by evaluation method 2.
[0176] "Example 9"
[0177] In a glove box with a dew point of about -75°C, zirconium sulfate (ZrSO4), zirconium chloride (ZrCl4), and lithium sulfate (Li2SO4) are weighed in a molar ratio of 0.5:1:1, and placed in a zirconia sealed container for a planetary ball mill with zirconia balls previously placed in it. Next, cover the sealed container, screw the lid to the container body, and further seal the lid and the container with polyimide tape. Polyimide tape has the effect of isolating moisture. Next, install the zirconia sealed container on the planetary ball mill. Set the rotation speed to 300 rpm and the revolution speed to 300 rpm, set the rotation direction of the rotation and the revolution direction to opposite directions, and carry out mechanochemical reaction for 5 hours to synthesize the solid electrolyte (Li2Zr 1.5 (SO4)2Cl).
[0178] Specifically, when the raw material powder is put into a sealed container made of zirconium oxide, Li2SO4 is crushed at a rotation speed of 300 rpm for 1 hour using the same planetary ball mill device as above before mixing. Then, ZrCl4 is added, and the mixture is further mixed and crushed at a rotation speed of 200 rpm for 1 hour. Then, the remaining raw material (ZrSO4 in Example 9) is added to complete the input.
[0179] Furthermore, the synthesis was performed while cooling the lid of the zirconia sealed container so that the amount of change in temperature became 10° C. or less one hour after the start of synthesis.
[0180] In Example 9, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 1, 2, and 7 below.
[0181] "Example 10"
[0182] In Example 10, a solid electrolyte was synthesized in the same manner as in Example 9, except that zirconium sulfate (ZrSO4), zirconium chloride (ZrCl4), and lithium sulfate (Li2SO4) were weighed so that the molar ratio was 0.4:1:1.5.
[0183] In Example 10, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 1, 2, and 7 below.
[0184] "Examples 11 to 21"
[0185] Examples 11 to 21 synthesized solid electrolytes in the same manner as Example 9 except that the materials and molar ratios of the raw material powders were changed. Physical properties of the solid electrolytes were measured in Examples 11 to 21 in the same manner as Example 9. The measurement results are summarized in Tables 1, 2, 7, and 8 below.
[0186] "Example 22"
[0187] In a glove box with a dew point of about -75°C, lithium oxide (Li2O) and zirconium chloride (ZrCl4) were weighed in a molar ratio of 10:1 and placed in a sealed container made of zirconium oxide for a planetary ball mill with zirconium oxide balls placed in advance. Then, the sealed container was closed, the lid was screwed to the container body, and the lid and the container were sealed with polyimide tape. Polyimide tape has the effect of isolating moisture.
[0188] Next, the sealed container made of zirconia was installed on a planetary ball mill. The rotation speed was set to 300 rpm and the revolution speed was set to 300 rpm. The rotation direction and the revolution direction were set to opposite directions. The mechanochemical reaction was performed for 4 hours to synthesize the solid electrolyte (Li10 ZrO5Cl4).
[0189] Specifically, when the raw material powder was placed in a sealed container made of zirconia, Li2O was pulverized at 300 rpm for 1 hour using the same planetary ball mill as described above before mixing. Next, the remaining raw material (ZrCl4 in Example 22) was added.
[0190] Furthermore, the synthesis was performed while cooling the lid of the zirconia sealed container so that the amount of change in temperature became 10° C. or less one hour after the start of synthesis.
[0191] In Example 22, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 3, 4, and 8 below.
[0192] "Examples 23 to 26"
[0193] Example 23 A solid electrolyte was synthesized in the same manner as in Example 22, except that the molar ratio of the raw material powders was changed and the synthesis time was set to 6 hours.
[0194] Example 24 A solid electrolyte was synthesized in the same manner as in Example 22, except that the molar ratio of the raw material powders was changed and the synthesis time was set to 24 hours.
[0195] Example 25 A solid electrolyte was synthesized in the same manner as in Example 22, except that the molar ratio of the raw material powders was changed and the synthesis time was set to 48 hours.
[0196] Example 26 A solid electrolyte was synthesized in the same manner as in Example 22, except that the molar ratio of the raw material powders was changed and the synthesis time was set to 72 hours.
[0197] In Examples 23 to 26, the physical properties of the solid electrolyte were measured in the same manner as in Example 22. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 3, 4, and 8 below.
[0198] In addition, Fig. 7A : A graph showing the evaluation of the Raman spectroscopic characteristics of the Raman spectrum of Example 25 by evaluation method 1. Figure 7B 2 is a graph showing the evaluation of the Raman spectral characteristics of the Raman spectrum of Example 25 by evaluation method 2.
[0199] "Examples 27 to 30"
[0200] In Examples 27 to 30, solid electrolytes were synthesized in the same manner as in Example 22 except that the materials and molar ratios of the raw material powders were changed. In Examples 23 to 30, the physical properties of the solid electrolytes were measured in the same manner as in Example 22. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 3, 4, and 8 below.
[0201] "Example 31"
[0202] In Example 31, a solid electrolyte was synthesized in the same manner as in Example 1, except that the raw material powder was charged and the container was sealed in a dry room with a dew point of -40°C. In Example 31, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in the following Tables 3, 4, and 8.
[0203] "Example 32"
[0204] In Example 32, a solid electrolyte was synthesized in the same manner as in Example 1, except that the raw material powder was charged and the container was sealed in a dry room with a dew point of -60°C. In Example 32, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in the following Tables 3, 4, and 8.
[0205] "Example 33"
[0206] In Example 33, a solid electrolyte was synthesized in the same manner as in Example 1 except that the molar ratio of the raw material powders was changed. In Example 33, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 3, 4, and 8 below.
[0207] "Comparative Example 1"
[0208] Comparative Example 1 was synthesized in the same manner as in Example 1 except that the material and molar ratio of the raw material powder were changed, the cooling of the zirconia container was not performed 1 hour after the start of synthesis, and the synthesis time was 24 hours. In addition, the change in the temperature of the lid of the zirconia sealed container became 20°C or more 1 hour after the start of synthesis. Comparative Example 1 was also measured in the same manner as in Example 1 for the physical properties of the solid electrolyte. The composition, molar ratio, and measurement results of each raw material are summarized in the following Tables 5, 6, and 9.
[0209] In addition, Figure 8 3 shows a graph showing evaluation of Raman spectroscopic characteristics of the Raman spectrum of Comparative Example 1 by Evaluation Method 1.
[0210] "Comparative Example 2"
[0211] Comparative Example 2 was synthesized in the same manner as in Example 1 except that the molar ratio of the raw material powder was changed, the cooling of the zirconia container was not performed 1 hour after the start of synthesis, and the synthesis time was 24 hours. In addition, the change in the temperature of the lid of the zirconia sealed container became 20°C or more 1 hour after the start of synthesis. Comparative Example 2 was also measured in the same manner as in Example 1 for the physical properties of the solid electrolyte. The composition, molar ratio, and measurement results of each raw material are summarized in the following Tables 5, 6, and 9.
[0212] In addition, Fig. 9 3 shows a graph showing evaluation of Raman spectroscopic characteristics of the Raman spectrum of Comparative Example 2 by Evaluation Method 1.
[0213] "Comparative Example 3"
[0214] In Comparative Example 3, a solid electrolyte was synthesized in the same manner as in Example 1, except that the raw material powder was charged and the container was sealed in a dry room with a dew point of -20°C, and the synthesis time was 5.5 hours. In Comparative Example 3, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in the following Tables 5, 6, and 9.
[0215] "Comparative Example 4"
[0216] In Comparative Example 4, a solid electrolyte was synthesized in the same manner as in Example 4, except that the cooling of the zirconia container was not performed 1 hour after the start of synthesis. In Comparative Example 4, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in the following Tables 5, 6, and 9.
[0217] "Comparative Example 5"
[0218] In Comparative Example 5, a solid electrolyte was synthesized in the same manner as in Example 4 except that the synthesis time was 24 hours. In Comparative Example 5, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 5, 6, and 9 below.
[0219] "Comparative Example 6"
[0220] In Comparative Example 6, a solid electrolyte was synthesized in the same manner as in Example 17, except that the cooling of the zirconia container was not performed 1 hour after the start of synthesis. In Comparative Example 6, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in the following Tables 5, 6, and 9.
[0221] "Comparative Example 7"
[0222] In Comparative Example 7, a solid electrolyte was synthesized in the same manner as in Example 18 except that the synthesis time was 24 hours. In Comparative Example 7, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 5, 6, and 9 below.
[0223] "Comparative Example 8"
[0224] In Comparative Example 8, a solid electrolyte was synthesized in the same manner as in Example 23 except that the synthesis time was 24 hours. In Comparative Example 8, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 5, 6, and 9 below.
[0225] "Comparative Example 9"
[0226] In Comparative Example 9, a solid electrolyte was synthesized in the same manner as in Example 24 except that the synthesis time was 48 hours. In Comparative Example 9, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 5, 6, and 9 below.
[0227] "Comparative Example 10"
[0228] In Comparative Example 10, a solid electrolyte was synthesized in the same manner as in Example 25, except that the cooling of the zirconia container was not performed 1 hour after the start of synthesis. Physical property values of the solid electrolyte were measured in Comparative Example 10 in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in the following Tables 5, 6, and 9.
[0229] "Comparative Example 11"
[0230] In Comparative Example 11, a solid electrolyte was synthesized in the same manner as in Example 26, except that the cooling of the zirconia container was not performed 1 hour after the start of synthesis. In Comparative Example 11, the physical properties of the solid electrolyte were measured in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in the following Tables 5, 6, and 9.
[0231] "Comparative Example 12"
[0232] In Comparative Example 12, a solid electrolyte was synthesized in the same manner as in Example 27 except that the synthesis time was 96 hours. Physical properties of the solid electrolyte were measured in Comparative Example 12 in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 5, 6, and 9 below.
[0233] "Comparative Example 13"
[0234] In Comparative Example 13, a solid electrolyte was synthesized in the same manner as in Example 33 except that the synthesis time was 72 hours. Physical properties of the solid electrolyte were measured in Comparative Example 13 in the same manner as in Example 1. The composition, molar ratio, and measurement results of each raw material are summarized in Tables 5, 6, and 9 below.
[0235] [Table 1]
[0236]
[0237] [Table 2]
[0238]
[0239] [Table 3]
[0240]
[0241] [Table 4]
[0242]
[0243] [Table 5]
[0244]
[0245] [Table 6]
[0246]
[0247] [Table 7]
[0248]
[0249] [Table 8]
[0250]
[0251] [Table 9]
[0252] (Fabrication of all-solid-state batteries)
[0253] The all-solid-state battery was made in a glove box with a dew point of about -70°C. The all-solid-state battery was made using a pellet making jig. The pellet making jig has a PEEK (polyetheretherketone) bracket with an inner diameter of 10 mm, and an upper punch and a lower punch with a diameter of 9.99 mm. The upper and lower punches are made of die steel (SKD11 material).
[0254] The lower punch was inserted into the PEEK holder of the pellet making jig, and 50 mg of solid electrolyte was placed on the lower punch. Next, the resin holder was vibrated to make the surface of the solid electrolyte flat. Next, the upper punch was inserted on the solid electrolyte, and a punching machine was used to press with a weight of about 4 kN.
[0255] Next, pull out the lower punch and drop 10 mg of the negative electrode mixture onto the solid electrolyte. Next, vibrate the PEEK bracket to level the surface of the negative electrode mixture. Next, insert the lower punch onto the negative electrode mixture and use a punch press to press with a weight of 3 kN. The negative electrode mixture consists of a negative electrode active material and the above-mentioned solid electrolyte. As the negative electrode active material, lithium titanate (LTO) with an average particle size of 6.0 μm is used. Next, pull out the upper punch and drop 10 mg of the positive electrode mixture onto the solid electrolyte layer. Next, vibrate the PEEK bracket to level the surface of the positive electrode mixture. Next, insert the upper punch onto the positive electrode mixture and use a punch press to press with a weight of 3 kN. The positive electrode mixture consists of a positive electrode active material, carbon as a conductive aid, and the above-mentioned solid electrolyte. As the positive electrode active material, lithium cobalt oxide (LCO) with an average particle size of 7.5 μm is used. In this way, a fully solid-state battery was produced in which the negative electrode mixture layer, the solid electrolyte layer, and the positive electrode mixture layer were stacked in this order.
[0256] In addition, two stainless steel plates with a diameter of 50 mm and a thickness of 5 mm and two Bakelite (registered trademark) plates with a diameter of 50 mm and a thickness of 2 mm were prepared. Next, four holes for screws to pass through were respectively provided on the two stainless steel plates and the two Bakelite (registered trademark) plates. The holes for screws to pass through were provided at a position where, when the electrochemical cell, the two stainless steel plates, and the two Bakelite (registered trademark) plates were stacked, the two stainless steel plates and the two Bakelite (registered trademark) plates overlapped when viewed from above, and did not overlap with the electrochemical cell when viewed from above.
[0257] Then, the stainless steel plate, Bakelite (registered trademark) plate, all-solid battery, Bakelite (registered trademark) plate, and stainless steel plate are stacked in sequence, and screws are inserted into the above-mentioned screw holes and tightened with a torque of 1 N·m. In this way, an all-solid battery in which the upper and lower punches of the electrochemical cell are insulated by the Bakelite (registered trademark) plate is obtained. Next, the all-solid battery is left to stand in a thermostatic chamber at 25°C for 48 hours to stabilize the open circuit voltage.
[0258] The rate characteristics are evaluated using the manufactured all-solid-state battery. The rate characteristics are evaluated based on the ratio of the discharge capacitance when discharged at a discharge rate of 1C to the discharge capacitance at a discharge rate of 0.1C (0.1C / 1C rate characteristics). The all-solid-state battery is subjected to constant current charging (CC charging) at a constant current rate of 0.1C at 25°C until the battery voltage reaches 2.7V. Then, after reaching 2.7V, charging (CV charging) is performed until the current becomes equivalent to 0.05C. Then, discharge (CC discharge) is performed at a constant current rate of 0.1C until the battery voltage reaches 1.5V, and the discharge capacitance at 0.1C is measured. Next, the all-solid-state battery is charged again under the above conditions, discharged at a discharge rate of 1C until the battery voltage reaches 1.5V, and the discharge capacitance at 1C is measured. The measurement results are summarized in Tables 7 to 9.
[0259] The compositions of Example 4, Comparative Examples 2, 4 and 5 are the same, but the conditions of the synthesis process are different. In Example 4, the zirconia container is cooled 1 hour after the start of synthesis, and the synthesis time is 5.5 hours. In contrast, in Comparative Example 2, the zirconia container is not cooled 1 hour after the start of synthesis, and the synthesis time is longer than that of Example 4, which is 24 hours. In addition, Comparative Example 4 is the same as Comparative Example 2, and the zirconia container is not cooled 1 hour after the start of synthesis, but the synthesis time is the same as that of Example 4, which is 5.5 hours. In addition, Comparative Example 5 is the same as Example 4, and the zirconia container is cooled 1 hour after the start of synthesis, but the synthesis time is longer than that of Example 4, which is 24 hours.
[0260] According to the different conditions of the synthesis process, the ion conductivity of Example 4, Comparative Example 2, Comparative Example 4 and Comparative Example 5 is 2.3×10 -3 〔S / cm〕、4.0×10 -4 〔S / cm〕、8.9×10 -4 〔S / cm〕、6.3×10 -4 [S / cm]. In addition, according to the magnitude of the ion conductivity, the rate characteristics of Example 4, Comparative Example 2, Comparative Example 4, and Comparative Example 5 are 80%, 30%, 54%, and 43%, respectively.
[0261] As described above, even if the composition is the same, the ion conductivity can be improved by adjusting the conditions of the synthesis step, and as a result, the rate characteristics can also be improved.
[0262] In Example 4, cooling was performed immediately after the start of synthesis, and optimization of the length of synthesis time was achieved. In Comparative Example 2, cooling was not performed immediately after the start of synthesis, and optimization of the length of synthesis time was not achieved. The ion conductivity of Example 4 was 5.8 times that of Comparative Example 2. In addition, in Comparative Example 4, although optimization of the length of synthesis time was achieved, cooling was not performed immediately after the start of synthesis. The ion conductivity of Example 4 was 2.6 times that of Comparative Example 4. In addition, in Comparative Example 5, although cooling was performed immediately after the start of synthesis, optimization of the length of synthesis time was not achieved. The ion conductivity of Example 4 was 3.7 times that of Comparative Example 5.
[0263] Example 17 and Comparative Example 6 have the same composition, but different synthesis process conditions. In Example 17, the zirconia container was cooled 1 hour after the start of synthesis. In contrast, in Comparative Example 6, the zirconia container was not cooled 1 hour after the start of synthesis.
[0264] According to the different conditions of the synthesis process, the ion conductivity of Example 17 and Comparative Example 6 is 2.5×10 -3 〔S / cm〕、9.2×10 -4 [S / cm]. In addition, according to the magnitude of the ion conductivity, the rate characteristics of Example 17 and Comparative Example 6 are 82% and 58%, respectively.
[0265] As described above, even if the composition is the same, the ion conductivity can be improved by adjusting the conditions of the synthesis step, and as a result, the rate characteristics can also be improved.
[0266] The ion conductivity of Example 17 in which cooling was performed immediately after the start of synthesis was 2.7 times the ion conductivity of Comparative Example 6 in which cooling was not performed immediately after the start of synthesis.
[0267] The compositions of Example 18 and Comparative Example 7 are the same, but the conditions of the synthesis process are different. In Example 18, the synthesis time is 5 hours. In contrast, in Comparative Example 7, the synthesis time is 24 hours.
[0268] According to the different conditions of the synthesis process, the ion conductivity of Example 18 and Comparative Example 7 is 2.7×10 -3 〔S / cm〕、9.5×10 -4 [S / cm]. In addition, according to the magnitude of the ion conductivity, the rate characteristics of Example 18 and Comparative Example 7 are 84% and 62%, respectively.
[0269] As described above, even if the composition is the same, the ion conductivity can be improved by adjusting the conditions of the synthesis step, and as a result, the rate characteristics can also be improved.
[0270] The ion conductivity of Example 18 in which the length of the synthesis time was optimized was 2.8 times the ion conductivity of Comparative Example 7 in which the length of the synthesis time was not optimized.
[0271] Example 23 and Comparative Example 8 have the same composition, but different synthesis process conditions. In Example 23, the synthesis time is 4 hours. In contrast, in Comparative Example 8, the synthesis time is 24 hours.
[0272] According to the different conditions of the synthesis process, the ion conductivity of Example 23 and Comparative Example 8 is 9.5×10 -4 〔S / cm〕、5.6×10 -4 [S / cm]. In addition, according to the magnitude of the ion conductivity, the rate characteristics of Example 23 and Comparative Example 8 are 69% and 39%, respectively.
[0273] As described above, even if the composition is the same, the ion conductivity can be improved by adjusting the conditions of the synthesis step, and as a result, the rate characteristics can also be improved.
[0274] The ion conductivity of Example 23 in which the length of the synthesis time was optimized was 3.6 times the ion conductivity of Comparative Example 8 in which the length of the synthesis time was not optimized.
[0275] The composition of Example 24 and Comparative Example 9 is the same, but the conditions of the synthesis process are different. In Example 24, the synthesis time is 4 hours. On the other hand, in Comparative Example 9, the synthesis time is 24 hours.
[0276] According to the different conditions of the synthesis process, the ion conductivity of Example 24 and Comparative Example 9 is 2.6×10 -3 〔S / cm〕, 7.7×10 -4 [S / cm]. In addition, according to the magnitude of the ion conductivity, the rate characteristics of Example 24 and Comparative Example 9 are 83% and 47%, respectively.
[0277] As described above, even if the composition is the same, the ion conductivity can be improved by adjusting the conditions of the synthesis step, and as a result, the rate characteristics can also be improved.
[0278] The ion conductivity of Example 24 in which the length of the synthesis time was optimized was 3.4 times the ion conductivity of Comparative Example 9 in which the length of the synthesis time was not optimized.
[0279] Example 25 and Comparative Example 10 have the same composition, but different synthesis process conditions. In Example 25, the zirconia container was cooled 1 hour after the start of synthesis. In contrast, in Comparative Example 10, the zirconia container was not cooled 1 hour after the start of synthesis.
[0280] According to the different conditions of the synthesis process, the ion conductivity of Example 25 and Comparative Example 10 is 3.2×10 -3 〔S / cm〕、9.8×10 -4 [S / cm]. In addition, according to the magnitude of the ion conductivity, the rate characteristics of Example 25 and Comparative Example 10 are 86% and 67%, respectively.
[0281] As described above, even if the composition is the same, the ion conductivity can be improved by adjusting the conditions of the synthesis step, and as a result, the rate characteristics can also be improved.
[0282] The ion conductivity of Example 25 in which cooling was performed immediately after the start of synthesis was 3.3 times the ion conductivity of Comparative Example 10 in which cooling was not performed immediately after the start of synthesis.
[0283] Example 26 and Comparative Example 11 have the same composition, but different synthesis process conditions. In Example 26, the zirconia container was cooled 1 hour after the start of synthesis. In contrast, in Comparative Example 11, the zirconia container was not cooled 1 hour after the start of synthesis.
[0284] According to the different conditions of the synthesis process, the ion conductivity of Example 26 and Comparative Example 11 is 2.3×10 -3 〔S / cm〕、8.2×10 -4 [S / cm]. In addition, according to the magnitude of the ion conductivity, the rate characteristics of Example 26 and Comparative Example 11 are 80% and 55%, respectively.
[0285] As described above, even if the composition is the same, the ion conductivity can be improved by adjusting the conditions of the synthesis step, and as a result, the rate characteristics can also be improved.
[0286] The ion conductivity of Example 26 in which cooling was performed immediately after the start of synthesis was 2.8 times the ion conductivity of Comparative Example 11 in which cooling was not performed immediately after the start of synthesis.
[0287] The compositions of Example 27 and Comparative Example 12 are the same, but the conditions of the synthesis process are different. In Example 27, the synthesis time is 48 hours. In contrast, in Comparative Example 12, the synthesis time is 96 hours.
[0288] According to the different conditions of the synthesis process, the ion conductivity of Example 27 and Comparative Example 12 is 2.5×10 -3 〔S / cm〕、5.8×10 -4 [S / cm]. In addition, according to the magnitude of the ion conductivity, the rate characteristics of Example 27 and Comparative Example 12 are 82% and 49%, respectively.
[0289] As described above, even if the composition is the same, the ion conductivity can be improved by adjusting the conditions of the synthesis step, and as a result, the rate characteristics can also be improved.
[0290] The ion conductivity of Example 27 in which the length of the synthesis time was optimized was 4.3 times the ion conductivity of Comparative Example 12 in which the length of the synthesis time was not optimized.
[0291] The compositions of Example 33 and Comparative Example 13 are the same, but the conditions of the synthesis process are different. The synthesis time of Example 33 is 48 hours. On the other hand, the synthesis time of Comparative Example 13 is 72 hours.
[0292] According to the different conditions of the synthesis process, the ion conductivity of Example 33 and Comparative Example 13 is 2.5×10 -3 〔S / cm〕、4.9×10 -4 [S / cm]. In addition, according to the magnitude of the ion conductivity, the rate characteristics of Example 33 and Comparative Example 13 are 82% and 49%, respectively.
[0293] As described above, even if the composition is the same, the ion conductivity can be improved by adjusting the conditions of the synthesis step, and as a result, the rate characteristics can also be improved.
[0294] The ion conductivity of Example 33 in which the length of the synthesis time was optimized was 4.3 times the ion conductivity of Comparative Example 13 in which the length of the synthesis time was not optimized.
[0295] Industrial Applicability
[0296] The solid electrolyte of the present embodiment can be suitably used in a solid electrolyte battery serving as a power source for electronic equipment.
Claims
1. A solid electrolyte, wherein: Contains a compound represented by the following formula (1), In the Raman spectrum detected by Raman spectroscopy, the -1 Range and 80~200cm -1 There is a peak in the range of 200-450cm -1 The peak in the range of 80 to 200 cm is defined as the peak A, and the straight line connecting the starting point 1A and the starting point 2A of the peak A is defined as the baseline A, and the -1 When the peak in the range of is set as peak B, and the straight line connecting starting point 1B and starting point 2B of the peak B is set as baseline B, the peak A relative to the strongest peak P from baseline A A The peak width at half the intensity is 55 cm -1 Above, and the peak B relative to the strongest peak P from the baseline B B The peak width at half the intensity is 55 cm -1 above; Li a A b HAVE BEEN c J e X f A h ···(1) In formula (1), A is at least one element selected from alkali metals and alkaline earth metals other than Li, E is at least one element selected from Al, Ga, In, Sc, Y, Ti, Zr, Hf, and lanthanide elements, J is at least one group selected from anions, X is at least one element selected from F, Cl, Br, and I, 0.5≦a<6, 0≦b<6, 0<c<2, 0<e≦6, 0<f≦6.1, and 0≦h≦0.
2.
2. The solid electrolyte according to claim 1, wherein The peak width of the peak B is 80 cm -1 above.
3. The solid electrolyte according to claim 1, wherein The wave number of the strongest peak in the peak B is 140 cm -1 the following.
4. The solid electrolyte according to claim 1, wherein In the Raman spectrum, In 400~1000cm -1 The straight line passing through the minimum point X and the second smallest minimum point Y in the region is set as the baseline C, and the strongest peak P of the peak part A is set as A and the strongest peak P of the peak portion B B When the intensities from the baseline C are IA and IB respectively, and the intensity between the peak A and the peak B at which the intensity from the baseline C becomes the minimum is IC, 0<IC.
5. The solid electrolyte according to claim 4, wherein The strongest peak P of the peak part A A The strength IA and strength IC satisfy 0.2≦IC / IA≦0.
6.
6. The solid electrolyte according to claim 4, wherein The strongest peak P of the peak B B The strength IB and strength IC satisfy 0.1≦IC / IB≦0.
6.
7. The solid electrolyte according to claim 4, wherein The strongest peak P of the peak part A A The intensity of IA and the strongest peak P of the peak B B The strength IB satisfies IA<IB.
8. The solid electrolyte according to claim 1, wherein The anion is selected from OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 、Si6O 18 、PO3、PO4、P2O7、P3O 10 , SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO, OOC-CH2-COO, OOC-CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH2-COO, C6H5SO3, OOC-CH=CH-COO, C(OH)(CH2COOH)2COO, AsO4, BiO4, CrO4, MnO4, PtF6, PtCl6, PtBr6, PtI6, SbO4, SeO4, TeO4, HCOO, CH3COO, O, Among them, BOB is the bis(oxalato)borate ion, OOC-(CH2)2-COO is the anion of succinic acid, OOC-CH2-COO is the anion of malonic acid, OOC-CH(OH)-CH(OH)-COO is the anion of tartaric acid, OOC-CH(OH)-CH2-COO is the anion of malic acid, C6H5SO3 is the anion of benzenesulfonic acid, OOC-CH=CH-COO (trans type) is the anion of fumaric acid, OOC-CH=CH-COO (cis type) is the anion of maleic acid, and C(OH)(CH2COOH)2COO is the anion of citric acid.
9. The solid electrolyte according to claim 1, wherein In the photoelectron spectrum measured by X-ray photoelectron spectroscopy (XPS), there are peaks at 170±0.5 eV (the chemical state of sulfur corresponds to SO 4 ) and 532±0.5 eV (the chemical state of oxygen corresponds to SO 4 ).
10. The solid electrolyte according to claim 1, wherein In the photoelectron spectrum measured by X-ray photoelectron spectroscopy (XPS), there are peaks at 132.5±0.5 eV (chemical state of phosphorus corresponds to PO 4 ) and 531.5±0.5 eV (chemical state of oxygen corresponds to PO 4 ).
11. A solid electrolyte layer, wherein: The invention comprises the solid electrolyte according to any one of claims 1 to 10.
12. A solid electrolyte battery, wherein: A solid electrolyte layer, a positive electrode, and a negative electrode are provided, wherein at least one of the positive electrode and the negative electrode comprises the solid electrolyte according to any one of claims 1 to 10.
13. A solid electrolyte battery, wherein: A method of manufacturing a solid electrolyte layer according to claim 11, a positive electrode, and a negative electrode.
Citation Information
Patent Citations
All-solid battery
JP2022122849A
Work transport apparatus and mapping method
JP2022157983A